La inclusión en la escuela, una oportunidad para aprender juntos - Molano Garavito, Luz Dary; Cely Rojas, Magda Zoraida (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The inclusion arouses all kind of emotions, feelings and opinions, many of those on favor and many against. However, its imposition overshadows the human vision that all this represents, not only in the school but in the society. This article pretends to aboard the legal parameters of the inclusion in the school system, visualizing, more than its compulsory character, the learning opportunity that generates the use of didactics in the acquisition and consolidation of writing and reading, and the determining role of the teacher that can make the difference in this process broadening the expectations about the subject, in order to consider this educational practices. It is an invitation to the reflection in the educative contexts to recognize the difference, accepting each one as an opportunity to learn together.